NILAI MORAL PANCASILA UNTUK MEMBANGUN DI ERA GLOBALISASI - Simatupang, Ester Paulina (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Writing this article aims to describe and explain the role, implementation and actualization of the values contained in each point of Pancasila in the era globalization in order to strengthen morals to build and advance the nation. In writing, this research was studied using qualitative methods or descriptive approaches in order to obtain discussion literature study obtained from various sources. After being the analysis, it is found that globalization is a thing that has an impact on changes in the order of people’s lives. In this case, Pancasila has a role to receive new incoming information so that the Indonesian nation, especially the younger generation, does not lose their identity, because the younger generation is expected to be able to continue the struggle in building and advancing the nation. With this it is necessary to instill Pancasila values to rebild and advance the nation.